PERIODE PERKEMBANGAN MEDIA MASSA - Aa Bambang A.S. (Jurnal Studi Komunikasi dan Media, 2014)
ABSTRACTMass Media constitutes the most appealing media to be observed. It is that the unbroken channel of communication to be discussed and learned, from Acta Diurna to mass communication. It is quite interesting to follow the journey of mass media from a period to another. This has come as the reason why the written begun. The used method is that the literature study. Despite the study is not a way major, on the depth and comprehensive meaning, but it is more expected to be such benchmark which is able to be the very first idea for emphasizing the study about “the history or the journey of media studies”, the practically rare thing – not to say never – to be done by bachelor in communication studies. The result of this research conducts the three periods of the journey of mass media, those are the past of mass communication, the present of mass communication, and the mass media studies. Each of the mentioned have the distinguished features, either from the main research aspect, the features of media, or the method within the study. Moreover, on the belonging and its regards to state-society, mass media takes the unique stance and absolutely determined. Keywords: Period; Mass Media. ABSTRAKMedia massa merupakan media yang paling menarik untuk dikaji.Sebagai saluran, ia tidak henti-hantinya dikaji dan didiskusikian, sejak Acta Diurnasampai komunikasi massa. Oleh karena itu, sangat menarik untuk mengikuti perkembangan media masa dari masa ke masa. Metode yang digunakan adalah kajian pustaka. Diharapkan, penelitian ini menjadi benchmarkyang menjadi idee awal untuk menekankan pentingnya kajian tentang perkembangan studi media. Kajian ini jarang –untuk tidak mengatakan tidak pernah- dilakukan oleh sarjana ilmu komunikasi. Hasil tinjauan ini menunjukkan bahwa ada 3 (tiga periode) tahap perkembangan media massa, yaitu : komunikasi mass masa lampau, komunikasi masa kini, dan studi tentang media massa. Setiap tahap memiliki karakteristik yang berbeda, baik aspek yang diteliti, karakteristik media itu sendiri, dan metode yang digunakan. Kata-kata Kunci: Periode;Media massa.